The Impact of Service Quality on Zakat Stakeholders Satisfaction: A Study on Malaysian Zakat Institutions - Abd Wahab, N.; Ibrahim, A. Z.; Zainol, Z.; Abu Bakar, M.; Minhaj, N. (Universiti Sains Islam Malaysia, 2024)
The purpose of this paper is to investigate the impact of service quality on zakat stakeholders’ satisfaction using an enhanced model appropriate for zakat institutions. A new and enhanced model (a combination of SERVQUAL and CARTER) was used to examine the the impact of service quality towards satisfaction from the perspective of zakat stakeholders. Data were collected from 799 respondents amongst zakat payers and zakat recipients. The paper utilizes the Structural Equation Modelling (SEM) in examining the impact of service quality towards satisfaction. The results show that Responsiveness & Compliance are the strongest indicators influencing the satisfaction of the zakat payers while Reliability is the strongest indicator influencing the satisfaction of the zakat recipients. The results of this study will be useful for zakat authority responsible for ensuring service delivery by the institutions.